Transcranial Direct Current Stimulation and Mindfulness for Cognitive and Mood Recovery in Stroke Survivors: A Pilot Randomized Controlled Study - Atekeh Mosannaei Najibi; Sama Rahnemayan; Alireza Poursoleimani; Rasoul Heshmati; Mohammad Ali Nazari; Erfan Golshan Shali; Ehsan Nasiri; Mehdi Farhoudi (Stroke Research and Treatment)
Trial Registration: ClinicalTrials.gov identifier: IRCT20090716002195N3